Functional profile of patients with traumatic brain injury at hospital discharge - Magalhães, Arieli Cristina; Guizzi Parisi, Aline; Nascimento, Bruna; Marques Tonella, Rodrigo; Mendes Camargo, Taís (O Mundo da Saúde, 2022)
The lesions caused by a Traumatic Brain Injury (TBI) of macro or micro character can physically and/or psychologically compromise an individual. Being a disease of modern society that affects any age, it is considered the main cause of morbidity and mortality in Brazil as it covers the economically active population. It can temporarily or permanently disable people, consequently generating an impact on their quality of life, and is difficult to measure their functional profile, level of recovery, and how long they will remain in a given profile. In order to determine and classify the functional profile of individuals with TBI at hospital discharge, an analytical, observational, and cross-sectional study was carried out in which the Glasgow Outcome Scale/Glasgow Extended Outcome Scale (GOSE) was applied through a form for data collection and interviews. The study population consisted of 26 volunteers, admitted for treatment at Hospital Universitario Sao Francisco de Braganca Paulista, Sao Paulo with a confirmed diagnosis of TBI through imaging tests between September 2019 and March 2020. We found evidence of 88.46 % belonging to the males, and 11.54% female, where the mean and standard deviation of age 35.73±16.76 were observed. Among the most common types of traumas, polytrauma stood out with 80.77% and GOSE had the highest scores where 46.15% had a score of 8. Most participants of the study were discharged from the HUSF with the functional profile of good recovery and may return to their lives before the trauma. Through functional classifications, it is possible to guide professionals responsible for the rehabilitation of those who were affected by trauma and were left with sequelae, as well as guide family members and community assistance centers.